2007
DOI: 10.1007/s00439-007-0453-9
|View full text |Cite
|
Sign up to set email alerts
|

Significant association of DRD1 with nicotine dependence

Abstract: Epidemiologic studies have strongly implicated genetics in smoking behavior. Genes in the dopaminergic system, which mediates the reinforcing and dependence-producing properties of nicotine, are plausible candidates for roles in nicotine dependence (ND). In this study, we examined five single-nucleotide polymorphisms (SNPs) within or near the dopamine D(1) receptor gene (DRD1) for their association with ND, which was assessed by smoking quantity (SQ), the Heaviness of Smoking Index (HSI), and the Fagerström Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 39 publications
2
91
1
3
Order By: Relevance
“…Our observation that the DRD1 markers (rs4532, rs686) are associated with the number of cigarettes smoked per day is in agreement with the results of Huang et al, who have identified the same DRD1 markers as being strongly associated with nicotine addiction (Huang et al, 2008b). Furthermore, the DRD1 rs686 marker has been identified by Huang et al as a functional polymorphism, likely affecting the expression of this gene (Huang et al, 2008b).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our observation that the DRD1 markers (rs4532, rs686) are associated with the number of cigarettes smoked per day is in agreement with the results of Huang et al, who have identified the same DRD1 markers as being strongly associated with nicotine addiction (Huang et al, 2008b). Furthermore, the DRD1 rs686 marker has been identified by Huang et al as a functional polymorphism, likely affecting the expression of this gene (Huang et al, 2008b).…”
Section: Discussionsupporting
confidence: 92%
“…To date, only one association study of DRD1 variants with nicotine addiction has been performed. Huang et al (2008b) found a significant association of two SNPs (rs686 and rs4532) with nicotine dependence, with the rs686 functional polymorphism likely affecting the expression of the dopamine D1 receptor.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…27 We also identified seven SNPs with Pp3.33 Â 10 À5 located near DRD1 on chromosome 5q35 (Figure 3). DRD1 has a role in behavior and psychiatric disorders, including schizophrenia, 28 autism, 29 attentiondeficit-hyperactivity disorder, 30 nicotine dependence 31 and alcohol dependence. 32 Among the top 30 SNPs for Neuroticism, three SNPs (rs265981, P ¼ 1.17 Â 10 À5 ; rs686, P ¼ 1.58 Â 10 À5 and rs4532, P ¼ 1.58 Â 10 À5 , Table 2 and Supplementary Table S1) were previously linked to psychiatric disorders.…”
Section: Neuroticismmentioning
confidence: 99%
“…Previous research had shown that the minor allele of rs4532 is more common in ADHD probands and predicted response and side-effects to drug treatment in schizophrenia, albeit associated with the DA antagonistic action of anti-psychotics rather than the agonistic action of stimulants (Bobb, Addington, Sidransky et al [15] ; Lai, Mo, Chen, Wang, Chen, Liao DL et al [16] ; Potkin, Basile, Jin, Masellis,Badri, Keator D et al [17] ). SNP rs4532 is located in the 5' UTR exon of the DRD1 gene and while its functional relevance is unclear, it may have affected DRD1 expression (Huang, Ma, Payne, Beuten, Dupont & Li [18] ).…”
Section: Autistic Flatness: Motor or Affective Effects?mentioning
confidence: 99%